Alexithymia mediates the pathway from negative life events to somatic symptoms: a cross-sectional study in a psychosomatic outpatient sample - Chen, Junjie; Ma, Dandan; Cao, Jinya; Wei, Jing (Frontiers in Psychiatry, 2026)
IntroductionSomatic Symptom Disorder (SSD), characterized by distressing and functionally impairing physical symptoms without adequate medical explanation, imposes substantial personal and socioeconomic burdens. While negative life events (NLEs) and alexithymia (difficulty identifying/describing emotions) are established risk factors for somatic symptoms, their interrelationships and underlying mechanisms remain inadequately explored. This study investigated whether alexithymia mediates the pathway between NLEs and somatic symptoms in a clinical sample.MethodsA cross-sectional analysis was conducted with 523 psychosomatic outpatients (65.2% female, mean age 41.45 ± 12.36 years) from Peking Union Medical College Hospital (2020-2025). Participants completed: 1) the Life Events Scale (LES) to assess NLE stress burden, 2) the Toronto Alexithymia Scale (TAS-26) to measure alexithymia (focusing on Difficulty Identifying Feelings [DIF] and Difficulty Describing Feelings [DDF]), and 3) the Patient Health Questionnaire-15 (PHQ-15) to quantify somatic symptom severity. Pearson correlations, linear regression, and mediation analyses (controlling for age/gender) examined relationships and mediating effects.ResultsNLEs and alexithymia were significantly correlated with somatic symptoms (r = 0.330 and r = 0.369, respectively, p<0.01). Linear regression confirmed both as significant predictors, explaining 11% and 13.6% of somatic symptom variance, respectively. Alexithymia subscales DIF (β = 0.220, p<0.001) and DDF (β = 0.141, p = 0.014) contributed significantly, while externally oriented thinking (EOT) did not. Crucially, mediation analysis revealed alexithymia partially mediated the NLEs-somatic symptoms pathway (indirect effect: B = 0.0028, 95% CI[0.001, 0.005]), accounting for 16.25% of the total effect. A bidirectional mediation effect was also observed, with NLEs mediating 11.9% of the alexithymia-somatic symptoms relationship.ConclusionAlexithymia significantly mediates the relationship between NLEs and somatic symptoms in psychosomatic outpatients, though its effect size (16.25%) suggests additional multifactorial pathways. Conversely, NLEs also partially mediate the alexithymia-symptom relationship, indicating complex bidirectional dynamics. Clinically, interventions targeting both alexithymia and NLE exposure may alleviate somatic symptom burden.